On the Forming of Methodological Fundamentals of Marxist Ethics - Kalenda, Česlovas (Problemos, 1979)
On the basis of materialistic conception of the essence of ideological process, objective, class sources of ethics in the period of rising capitalism (the ethics of “reasonable egoism” of the French Enlighteners of the 18th century as well as the Hegelian objectivistic conception of ethics) are investigated. Thus the social reasons for the rise of a new, Marxist theory of ethics is explained, its methodological novelty is shown and its link with preceding ethics is revealed.